If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + a) * 6 = 12a + -12 Reorder the terms for easier multiplication: 6(3 + a) = 12a + -12 (3 * 6 + a * 6) = 12a + -12 (18 + 6a) = 12a + -12 Reorder the terms: 18 + 6a = -12 + 12a Solving 18 + 6a = -12 + 12a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12a' to each side of the equation. 18 + 6a + -12a = -12 + 12a + -12a Combine like terms: 6a + -12a = -6a 18 + -6a = -12 + 12a + -12a Combine like terms: 12a + -12a = 0 18 + -6a = -12 + 0 18 + -6a = -12 Add '-18' to each side of the equation. 18 + -18 + -6a = -12 + -18 Combine like terms: 18 + -18 = 0 0 + -6a = -12 + -18 -6a = -12 + -18 Combine like terms: -12 + -18 = -30 -6a = -30 Divide each side by '-6'. a = 5 Simplifying a = 5
| -(8y+2)-(-7y-6)=-1 | | 8X=-20+6Y | | a-10=3 | | 2x^2-8x-42=68 | | -3*3.14+w=2*3.14 | | 8-(4x+2)=28 | | 5y=-8x-2 | | x^4+6x^3-2x^2-12x=0 | | 12.00-2.00h=10 | | -3*3.14+w=23.14 | | x/12=30/20 | | 6(x+5)+8=2x | | 4(4x-5)=2(8x-10) | | n/8*10/4=0 | | n/8*10/4= | | x^2-3x+54=0 | | 4t-13=2x+9 | | x-1=x+3 | | 15-6x=45 | | y+2=-7(x+3) | | y-2=x+2 | | 0.5(3x-4)=4 | | 23=4n+11 | | 52+3=14-6n | | t=2k+2w | | 10-y-3y=7y-23 | | 2x-22=6x+18 | | 4(x+n)=x | | 2x(x+3)-7=4x-6 | | Y=9y-72 | | 2(4x-1)+3(3-2x)= | | n+3=5n |